The economic impact of next generation EU: A euro area perspective - Krzysztof Bańkowski; Othman Bouabdallah; Jo\~ao Domingues Semeano; Ettore Dorrucci; Maximilian Freier; Pascal Jacquinot; Wolfgang Modery; Marta Rodríguez Vives; Vilém Valenta; Nico Zorell (European Central Bank (ECB), 2022)
This paper assesses the potential economic impact of Next Generation EU (NGEU), focusing on the euro area. Its findings suggest that the envisaged national investment and reform plans present a coherent package to support both recovery from the pandemic-induced crisis and longer-term modernisation of the euro area economy through their digital and green transitions. NGEU, however, can only unfold its full potential if all plans are implemented in a timely and effective way. We estimate the impact of the national plans on output, inflation and public debt using ECB staff economic models under the assumption of successful implementation. Specifically, NGEU is expected to take effect through three channels: structural reform, fiscal stimulus and risk premium. Overall, NGEU may increase gross domestic product (GDP) in the euro area by up to 1.5% by 2026, with the impact expected to be significantly larger in the main beneficiary countries. In Italy and Spain, two of the main beneficiaries, the public debt-to-GDP ratio may be more than 10 percentage points lower by 2031. At the same time, all euro area countries are expected to benefit from NGEU through positive spillovers, greater economic resilience and convergence across countries. Finally, the effect of NGEU on euro area inflation over the medium term is deemed to be contained to the extent that the inflationary effect of additional public expenditure is offset, at least to some degree, by the disinflationary effect of greater productive capacity resulting from the planned structural reform and investment measures.
Keywords: C54; E02; E22; E62; F45; H87; O52; 330; Next Generation EU (NGEU); Recovery and Resilience Facility (RRF); public investment; structural reform